2008
DOI: 10.1111/j.1365-2141.2008.07393.x
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent non‐Hodgkin lymphoma and Hodgkin lymphoma: state of the science

Abstract: SummaryLymphoma is the most common malignancy among adolescents, accounting for >25% of newly diagnosed cancers in the 15-19 year age group. Hodgkin lymphoma (HL) accounts for the majority (two-thirds) of cases, while the remainder of patients have one of four subtypes of non-Hodgkin lymphoma (NHL): diffuse large B-cell lymphoma (DLBCL) including primary mediastinal B-cell lymphoma (PMBL), Burkitt lymphoma (BL), lymphoblastic lymphoma (LL) or anaplastic large cell lymphoma (ALCL). Epidemiology, histology, trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
1
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 110 publications
(158 reference statements)
2
83
1
4
Order By: Relevance
“…Our results are comparable to those of Peko et al in Congo who reported a rate of 20% of retinoblastoma and 9.2% of Nephroblastoma (Peko et al, 2004). Nephroblastoma is a fairly common tumor in children in Africa, affects both sexes almost equally, and can be associated with various renal such as nephroblastomatosis or extrarenal malformations including urogenital malformations and Wiedeman syndrome -Beckwith (Hochberg et al, 2009). Retinoblastoma usually appears in children before the age of five years who had two alleles of the RB1 gene disease transmitted as on an autosomal dominant mode, and half of retinoblastoma is diagnosed before the age of two years (Packer et al, 2010).…”
Section: 81 Evaluation Of the Histo-epidemiological Profile Of Solidmentioning
confidence: 99%
“…Our results are comparable to those of Peko et al in Congo who reported a rate of 20% of retinoblastoma and 9.2% of Nephroblastoma (Peko et al, 2004). Nephroblastoma is a fairly common tumor in children in Africa, affects both sexes almost equally, and can be associated with various renal such as nephroblastomatosis or extrarenal malformations including urogenital malformations and Wiedeman syndrome -Beckwith (Hochberg et al, 2009). Retinoblastoma usually appears in children before the age of five years who had two alleles of the RB1 gene disease transmitted as on an autosomal dominant mode, and half of retinoblastoma is diagnosed before the age of two years (Packer et al, 2010).…”
Section: 81 Evaluation Of the Histo-epidemiological Profile Of Solidmentioning
confidence: 99%
“…Anaplastic large cell lymphoma (ALCL) represents approximately 15% of all pediatric non-Hodgkin lymphomas (NHL) [1]. First described by Stein et al [2], ALCL is characterized by proliferation of anaplastic cells of T or null phenotype with CD30 antigen expression.…”
Section: Introductionmentioning
confidence: 99%
“…1 alone [21] to intensified therapy with hematopoietic stem cell transplantation (HSCT) [17,[22][23][24][25], resulting in high overall survival (OS) rate. Here, we report the characteristics and longterm outcome of ALCL patients treated in the Italian Association of Pediatric Hematology and Oncology (AIEOP) centers using AIEOP LNH-97 protocol.…”
Section: Introductionmentioning
confidence: 99%
“…This is less of an issue in BL, however as similar regimens are used for all patients but the elderly. It is worth noting however that adolescents generally fare only marginally worse than children treated on the same protocols (Burkhardt et al, 2011) and in the French-AmericanBritish (FAB)/LMB 96 trial the excess failure in adolescents compared to children could be accounted for by the distribution of stage and sites of disease (Hochberg et al, 2009). This trial clearly demonstrated that reductions in therapy were possible without detriment to good risk patients and this can be reasonably extrapolated to the adolescent population.…”
Section: Adolescent Patientsmentioning
confidence: 99%